Laboratory and clinical studies on S-1108 - Arita, Kenichi; Daido, Kazuhiro; Yamakido, Michio; Hozawa, Soichiro (CHEMOTHERAPY, 1993)
The efficacy and safety of the new ester-type oral cephem antibiotic S-1108 was studied in treating various infections. There were 20 subjects (13 males and 7 females) ranging in age from 29 to 77 years (mean age: 59.7 years). The target diseases included pneumonia in 5 cases, bronchitis in 2 cases, acute exacerbation of chronic bronchitis in 4 cases, bronchial asthma+lower respiratory infection in 2 cases, bronchiectasis and acute exacerbation of chronic pulmonary emphysema in 2 cases, upper respiratory tract infection in 3 cases, and periproctitis and cystitis in 1 case each, for a total of 20 cases. S-1108 was administered 3 times daily in doses of 100 mg, and the treatment period ranged from 3 to 25 days (mean 10.5days). S-1108 was judged effective in 14 cases, fair in 3 cases, poor in 2 cases, and in 1 case was unevaluable, for an efficacy rate of 73.7%. In 7 of the 8 cases evaluated for bacteriological efficacy the bacteria were eliminated. Side effects consisted of dizziness in 1 patient. No abnormal changes in laboratory findings were observed.